INDIRECT TAX ADMINISTRATION AND GOVERNMENT REVENUE GENERATION IN NIGERIA (Journal of Global Accounting, 2023)
This study examined indirect tax administration and government revenue generation in Nigeria. Specifically, the study sought to ascertain how  Value Added Tax, and Customs and excise duty  as proxies for indirect tax administration affects government revenue generation in Nigeria. Time series data for 22 years spanning from 2000 to 2021 were sourced from secondary sources including FIRS annual reports, CBN bulletin and National bureau of statistics (NBS) reports. The study adopted ex-post facto research design, and the formulated hypotheses were tested using ordinary least square regression (OLS) at 5% significant level and by way of preliminary test, augmented dickey fuller (unit root) test was used to ascertain the stationary state of the time series variables. The results of the analysis revealed that all the variables have a joint significant influence on the total government revenue generation in Nigeria at 5% significant level. While specifically, Value Added Tax have a positive significant effect on total revenue generation while  Customs and Excise Duties showed both negative and non-significant effect on total revenue generation in Nigeria. The study recommends amongst others that government through FIRS should double efforts to sustain appreciable level of revenue via value tax by capturing all informal economic activities that may hinder collection of VAT and secondly, government should re-orientate the Nigerian Custom Service via rigorous training to improve their skills and knowledge and also ensure strict implementation of the Nigerian Custom Service reforms to curb loopholes through which revenue flow out.
Keywords: Indirect tax; Tax administration; Government revenue